Conductive PE material with good shock resistance and low resistance and preparation method thereof
By adding SBS elastomer, triethanolamine quaternary ammonium styrene grafted polyethylene and carboxylated carbon nanotubes to the polyethylene resin, melt blending is performed using the combined process of a mixer and a twin-screw extruder, the problems of poor impact resistance, conductivity and antistatic properties of the polyethylene material are solved, and efficient enhancement and performance improvement of the material are achieved.
Patent Information
- Application Number
- CN202510056513.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-14
AI Technical Summary
Polyethylene materials have poor impact resistance, conductivity and antistatic properties.
Using 100 parts by weight of polyethylene resin, 10-35 parts by weight of SBS elastomer, 1.2-5 parts by weight of triethanolamine quaternary ammonium styrene grafted polyethylene, 1-6 parts by weight of carboxylated carbon nanotubes and 0.3-0.5 parts by weight of antioxidant, the conductive PE material with good seismic resistance and low resistance was prepared.
The impact strength, bending strength and conductive properties of polyethylene materials are significantly improved, while reducing the surface resistance of the material and enhancing the anti-static properties.
Smart Images

Figure BDA0005241589300000021 
Figure BDA0005241589300000071 
Figure BDA0005241589300000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyethylene, in particular to a conductive PE material with good shock resistance and low resistance and a preparation method thereof. Background Art
[0002] Polyethylene resin is odorless, non-toxic, has good low temperature resistance and low cost. It is widely used in films, packaging, containers, pipelines, wires and cables, etc. It is of great significance to improve the mechanical properties of polyethylene materials such as impact resistance, bending resistance and seismic resistance, as well as electrical conductivity and antistatic properties. SBS elastomer is a triblock copolymer composed of styrene and butadiene. It is a thermoplastic elastomer with excellent performance and can improve the mechanical properties of polymer materials such as polyethylene, asphalt, epoxy resin, polyurethane, etc.
[0003] Adding inorganic nanomaterials such as carbon nanotubes, nano-silicon dioxide, and nano-zinc oxide to polyethylene can improve the mechanical strength, antistatic and other properties of the material. Chinese patent CN114213744B discloses an antistatic packaging material, which uses polyvinyl alcohol-modified multi-walled carbon nanotubes as an antistatic agent, has good compatibility with linear low-density polyethylene, and improves the mechanical properties and antistatic properties of the packaging material. Compared with the invention patent, the present invention not only reduces the surface resistance of the polyethylene material and improves the antistatic / conductive properties, but also uses SBS elastomer to improve the bending strength, impact strength and other properties of the polyethylene resin. Summary of the invention
[0004] The invention solves the problem that the polyethylene material has poor performances such as impact resistance, conductivity and antistatic properties.
[0005] The technical scheme adopted by the present invention is: a conductive PE material with good shock resistance and low resistance, comprising 100 parts by weight of polyethylene resin, 10-35 parts by weight of SBS elastomer, 1.2-5 parts by weight of triethanolamine quaternary ammonium salt styrene grafted polyethylene, 1-6 parts by weight of carboxylated carbon nanotubes, and 0.3-0.5 parts by weight of antioxidant.
[0006] Furthermore, the preparation method of the conductive PE material with good shock resistance and low resistance is: polyethylene resin, SBS elastomer, triethanolamine quaternary ammonium salt styrene grafted polyethylene, carboxylated carbon nanotubes, and antioxidant are mixed in a mixer, and then melt-mixed, extruded, and pelletized in a twin-screw extruder to obtain the conductive PE material with good shock resistance and low resistance.
[0007] Furthermore, the temperature of the mixer is 60-70°C and the mixing time is 20-40 min; the melt blending temperature of the twin-screw extruder is 180-190°C and the screw speed is 60-100 r / min.
[0008] Furthermore, the preparation method of triethanolamine quaternary ammonium salt styrene grafted polyethylene is as follows: polyethylene resin, 4-vinylbenzyl triethanolamine quaternary ammonium salt, and diisopropylbenzene peroxide in a mass ratio of 100:(4-15):(0.2-0.8) are added to a twin-screw extruder, melt-grafted at 175-185° C. for 4-8 minutes, discharged, the product is added to xylene, heated to 140° C. and refluxed, stirred for 4-6 hours until dissolved, and then acetone is added for precipitation, the precipitate is extracted with acetone in a Soxhlet extractor, and dried to obtain triethanolamine quaternary ammonium salt styrene grafted polyethylene.
[0009] Further, the preparation method of 4-vinylbenzyltriethanolamine quaternary ammonium salt is as follows: 4-chloromethylstyrene and triethanolamine in a molar ratio of 1: (1-1.05) are added to acetonitrile, heated to 40-55° C. in a nitrogen atmosphere, reacted for 18-30 hours, concentrated under reduced pressure, and the product was recrystallized from a mixed solution of ethanol and ethyl acetate to obtain 4-vinylbenzyltriethanolamine quaternary ammonium salt. The reaction formula is:
[0010]
[0011] Furthermore, the preparation method of carboxylated carbon nanotubes is as follows: add carbon nanotubes to a nitric acid solution with a mass fraction of 60-68%, heat to 50-60°C after ultrasonic dispersion, react for 1-2 hours, filter after cooling, add the product to a sodium hydroxide solution, filter after stirring, wash with water, and dry to obtain carboxylated carbon nanotubes.
[0012] The technical effect of the present invention is as follows: 4-vinylbenzyltriethanolamine quaternary ammonium salt is used to perform melt grafting modification on polyethylene resin to obtain quaternary ammonium salt styrene grafted polyethylene, which is then melt extruded with polyethylene resin and SBS elastomer to obtain a conductive PE material with good shock resistance and low resistance. The quaternary ammonium salt styrene grafted polyethylene contains a polyethylene main chain, and a polystyrene molecular chain is grafted on a side chain. The polyethylene main chain has good compatibility with the polyethylene resin, and the polystyrene molecular chain also has similar polarity to the styrene block molecular chain in the SBS elastomer, so that the quaternary ammonium salt styrene grafted polyethylene plays the role of a compatibilizer, further improves the compatibility between the SBS elastomer and the polyethylene resin, makes the SBS elastomer play a good toughening effect, and is conducive to improving the toughness and mechanical properties of the polyethylene resin.
[0013] The quaternary ammonium salt styrene grafted polyethylene contains quaternary ammonium salt cation groups, which can interact with the sodium carboxylate anions on the surface of the carboxylated carbon nanotubes to form anion-cation bonds, so that the quaternary ammonium salt styrene grafted polyethylene is modified on the surface of the carbon nanotubes, thereby improving the dispersibility of the carbon nanotubes, improving the compatibility between the carbon nanotubes and the SBS elastomer and the polyethylene resin, making the carbon nanotubes play a good reinforcing role, and further improving the bending strength and impact strength of the PE material.
[0014] The carboxylated carbon nanotubes of the invention are uniformly dispersed in a material matrix under the modification of the quaternary ammonium salt styrene grafted polyethylene to form a continuous conductive network, which is beneficial to reducing the resistance and conductive performance of the PE material; meanwhile, the quaternary ammonium salt styrene grafted polyethylene contains quaternary ammonium salt and polyhydroxy hydrophilic groups, which improves the surface hydrophilicity of the PE material, can absorb moisture in the air, form a conductive layer, and is beneficial to reducing surface resistance and preventing static electricity accumulation, thereby improving conductive performance and antistatic performance. DETAILED DESCRIPTION
[0015] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0016] The polyethylene resin in the specific implementation and examples is DMDA-8920, from Shanghai Handar New Materials Co., Ltd. SBS elastomer is YH-1401, from Dongguan Lingxing Plastic Raw Materials Co., Ltd. Carbon nanotubes, with a length specification of 0.5-2 um, from Zhongke Leiming (Beijing) Technology Co., Ltd.
[0017] Embodiment 1:
[0018] (1) 0.5 g of carbon nanotubes were added to 250 mL of 68% nitric acid solution, and the mixture was ultrasonically dispersed and heated to 50° C. for 2 h. The mixture was cooled and filtered. The product was added to 10% sodium hydroxide solution, stirred for 30 min, filtered, washed with water, and dried to obtain carboxylated carbon nanotubes.
[0019] (2) Add 20 mmol of 4-chloromethylstyrene and 20 mmol of triethanolamine to 20 mL of acetonitrile, heat to 40° C. in a nitrogen atmosphere, react for 30 h, and concentrate under reduced pressure. The product is recrystallized from a mixed solution of ethanol and ethyl acetate to obtain 4-vinylbenzyltriethanolamine quaternary ammonium salt.
[0020] (3) 50 g of polyethylene resin, 2 g of 4-vinylbenzyltriethanolamine quaternary ammonium salt, and 0.1 g of diisopropylbenzene peroxide are added to a twin-screw extruder, melt-grafted at 180° C. for 4 min, and the product is added to xylene, heated to 140° C. and refluxed, stirred for 4 h until dissolved, and then acetone is added for precipitation. The precipitate is extracted with acetone in a Soxhlet extractor and dried to obtain triethanolamine quaternary ammonium salt styrene grafted polyethylene.
[0021] (4) 1 kg of polyethylene resin, 100 g of SBS elastomer, 12 g of triethanolamine quaternary ammonium salt styrene grafted polyethylene, 10 g of carboxylated carbon nanotubes, and 3 g of antioxidant 1010 were mixed in a mixer at 60° C. for 40 min, and then melt-mixed in a twin-screw extruder, with the temperature controlled at 180° C. and the screw speed at 100 r / min, extruded, and pelletized to obtain a conductive PE material with good shock resistance and low resistance.
[0022] Comparative Example 1:
[0023] (1) 1 kg of polyethylene resin, 100 g of SBS elastomer, and 3 g of antioxidant 1010 were mixed in a mixer at 60° C. for 40 min, and then melt-mixed in a twin-screw extruder with the temperature controlled at 180° C. and the screw speed at 100 r / min, extruded, and pelletized to obtain a PE material.
[0024] Comparative Example 2:
[0025] (1) 1 kg of polyethylene resin, 100 g of SBS elastomer, 12 g of triethanolamine quaternary ammonium salt styrene grafted polyethylene (prepared according to the method of Example 1), and 3 g of antioxidant 1010 were mixed in a mixer at 60° C. for 40 min, then melt-mixed in a twin-screw extruder with the temperature controlled at 180° C. and the screw speed at 100 r / min, extruded, and pelletized to obtain a PE material.
[0026] Comparative Example 3:
[0027] (1) 1 kg of polyethylene resin, 100 g of SBS elastomer, 10 g of carboxylated carbon nanotubes (prepared according to the method of Example 1), and 3 g of antioxidant 1010 were mixed in a mixer at 60° C. for 40 min, then melt-mixed in a twin-screw extruder, the temperature was controlled at 180° C., the screw speed was 100 r / min, extruded, and pelletized to obtain a conductive PE material with good shock resistance and low resistance.
[0028] Comparative Example 4:
[0029] (1) 50 g of polyethylene resin, 2 g of styrene, and 0.1 g of diisopropylbenzene peroxide are added to a twin-screw extruder, melt-grafted at 180° C. for 4 min, and the product is added to xylene, heated to 140° C. and refluxed, stirred for 4 h until dissolved, and then acetone is added for precipitation. The precipitate is extracted with acetone in a Soxhlet extractor and dried to obtain styrene-grafted polyethylene.
[0030] (2) 1 kg of polyethylene resin, 100 g of SBS elastomer, 12 g of styrene-grafted polyethylene, 10 g of carboxylated carbon nanotubes (prepared according to the method of Example 1), and 3 g of antioxidant 1010 were mixed in a mixer at 60° C. for 40 min, then melt-mixed in a twin-screw extruder, the temperature was controlled at 180° C., the screw speed was 100 r / min, and the mixture was extruded and pelletized to obtain a conductive PE material with good shock resistance and low resistance.
[0031] Comparative Example 5:
[0032] (1) 1 kg of polyethylene resin, 100 g of SBS elastomer, 12 g of triethanolamine quaternary ammonium salt styrene grafted polyethylene (prepared according to the method of Example 1), 10 g of carbon nanotubes, and 3 g of antioxidant 1010 were mixed in a mixer at 60° C. for 40 min, then melt-mixed in a twin-screw extruder, the temperature was controlled at 180° C., the screw speed was 100 r / min, extruded, and pelletized to obtain a conductive PE material with good shock resistance and low resistance.
[0033] Comparative Example 6:
[0034] (1) 50 g of polyethylene resin and 2 g of N-triethyl-(4-vinylbenzyl)ammonium chloride (CAS No. 14350-43-7, structural formula: ), 0.1g of diisopropylbenzene peroxide was added into a twin-screw extruder, melt-grafted at 180°C for 4 minutes, and the product was added into xylene, heated to 140°C and refluxed, stirred for 4 hours until dissolved, and then acetone was added for precipitation. The precipitate was extracted with acetone in a Soxhlet extractor and dried to obtain quaternary ammonium salt styrene grafted polyethylene.
[0035] (2) 1 kg of polyethylene resin, 100 g of SBS elastomer, 12 g of quaternary ammonium salt styrene grafted polyethylene, 10 g of carboxylated carbon nanotubes (prepared according to the method of Example 1), and 3 g of antioxidant 1010 were mixed in a mixer at 60° C. for 40 min, then melt-mixed in a twin-screw extruder, the temperature was controlled at 180° C., the screw speed was 100 r / min, and the mixture was extruded and pelletized to obtain a conductive PE material with good shock resistance and low resistance.
[0036] Embodiment 2:
[0037] (1) 0.5 g of carbon nanotubes were added to 300 mL of 60% nitric acid solution, and the mixture was ultrasonically dispersed and heated to 60° C. The mixture was reacted for 1 h, cooled and filtered, and the product was added to 10% sodium hydroxide solution, stirred for 30 min, filtered, washed with water, and dried to obtain carboxylated carbon nanotubes.
[0038] (2) Add 20 mmol 4-chloromethylstyrene and 21 mmol triethanolamine to 20 mL acetonitrile, heat to 55° C. in a nitrogen atmosphere, react for 18 h, and concentrate under reduced pressure. The product is recrystallized from a mixed solution of ethanol and ethyl acetate to obtain 4-vinylbenzyltriethanolamine quaternary ammonium salt.
[0039] (3) 50 g of polyethylene resin, 4.8 g of 4-vinylbenzyltriethanolamine quaternary ammonium salt, and 0.25 g of diisopropylbenzene peroxide are added to a twin-screw extruder, melt-grafted at 175° C. for 8 min, and the product is added to xylene, heated to 140° C. and refluxed, stirred for 6 h until dissolved, and then acetone is added for precipitation. The precipitate is extracted with acetone in a Soxhlet extractor and dried to obtain triethanolamine quaternary ammonium salt styrene grafted polyethylene.
[0040] (4) 1 kg of polyethylene resin, 220 g of SBS elastomer, 30 g of triethanolamine quaternary ammonium salt styrene grafted polyethylene, 30 g of carboxylated carbon nanotubes, and 5 g of antioxidant 1010 were mixed in a mixer at 70° C. for 40 min, and then melt-mixed in a twin-screw extruder, with the temperature controlled at 190° C. and the screw speed at 100 r / min, extruded, and pelletized to obtain a conductive PE material with good shock resistance and low resistance.
[0041] Embodiment 3:
[0042] (1) 50 g of polyethylene resin, 7.5 g of 4-vinylbenzyltriethanolamine quaternary ammonium salt (prepared according to the method of Example 1), and 0.4 g of diisopropylbenzene peroxide were added to a twin-screw extruder, melt-grafted at 185° C. for 5 min, and the product was added to xylene, heated to 140° C. and refluxed, stirred for 4 h until dissolved, and then acetone was added for precipitation. The precipitate was extracted with acetone in a Soxhlet extractor and dried to obtain triethanolamine quaternary ammonium salt styrene grafted polyethylene.
[0043] (2) 1 kg of polyethylene resin, 350 g of SBS elastomer, 50 g of triethanolamine quaternary ammonium salt styrene grafted polyethylene, 60 g of carboxylated carbon nanotubes (prepared according to the method of Example 1), and 4 g of antioxidant 1010 were mixed in a mixer at 60° C. for 40 min, and then melt-mixed in a twin-screw extruder with the temperature controlled at 185° C. and the screw speed at 60 r / min, extruded, and pelletized to obtain a conductive PE material with good shock resistance and low resistance.
[0044] The PE material is injection molded by an injection molding machine to form a standard specimen, and the bending performance is tested according to the national standard GB / T 9341-2008. The impact performance is tested according to the national standard GB / T 1043.1-2008.
[0045] The surface resistance of PE material was tested according to GB / T 1410-2006 method. The test temperature was 25℃.
[0046] Table 1
[0047]
[0048]
[0049] As can be seen from the above table, the PE material of Example 1 has high bending strength and impact strength, and has better toughness, impact resistance, bending and shock resistance, mainly because SBS elastomer, quaternary ammonium salt styrene grafted polyethylene and carboxylated carbon nanotubes are added. The quaternary ammonium salt styrene grafted polyethylene contains a polyethylene main chain, and the side chain is grafted with a polystyrene molecular chain. The polyethylene main chain has good compatibility with the polyethylene resin, and the polystyrene molecular chain and the styrene block molecular chain in the SBS elastomer also have similar polarity, so that the quaternary ammonium salt styrene grafted polyethylene plays the role of a compatibilizer, further improving the SBS elastomer and the poly The compatibility between ethylene resins makes SBS elastomer play a good toughening effect, which is conducive to improving the toughness and mechanical properties of polyethylene resin, and the quaternary ammonium salt styrene grafted polyethylene contains quaternary ammonium salt cationic groups, which can interact with the carboxylic acid sodium salt anions on the surface of carboxylated carbon nanotubes to form anionic and cationic bonds, so that the quaternary ammonium salt styrene grafted polyethylene is modified on the surface of carbon nanotubes, improving the dispersibility of carbon nanotubes, improving the compatibility between carbon nanotubes and SBS elastomers and polyethylene resins, making carbon nanotubes play a good reinforcing role, and further improving the bending strength and impact strength of PE materials. In addition, the carbon nanotubes are evenly dispersed in the material matrix to form a continuous conductive network, which is conducive to reducing the resistance and conductive properties of PE materials. At the same time, the quaternary ammonium salt styrene grafted polyethylene contains quaternary ammonium salts and polyhydroxy hydrophilic groups, which improve the surface hydrophilicity of PE materials, can absorb moisture in the air, form a conductive layer, and are conducive to reducing surface resistance and preventing static electricity accumulation, thereby improving conductive properties and antistatic properties.
[0050] Comparative Example 1 does not add quaternary ammonium salt styrene grafted polyethylene and carboxylated carbon nanotubes, does not improve the compatibility between polyethylene resin and SBS elastomer, and the surface resistance of PE material is large, and the antistatic and conductive properties are poor.
[0051] Comparative Example 2 adds triethanolamine quaternary ammonium salt styrene grafted polyethylene, which can improve the compatibility between polyethylene resin and SBS elastomer, and the bending strength and impact strength of the PE material are significantly improved, and the surface resistance is reduced. This is mainly because the triethanolamine quaternary ammonium salt styrene grafted polyethylene contains quaternary ammonium salt and polyhydroxy hydrophilic groups, which can improve the surface hydrophilicity of the PE material, absorb moisture in the air, form a conductive layer, and help reduce the surface resistance, which is lower than that of Comparative Example 1.
[0052] Comparative Example 3 did not add quaternary ammonium salt styrene grafted polyethylene, and did not improve the compatibility among the carboxylated carbon nanotubes, polyethylene resin and SBS elastomer, resulting in lower bending strength and impact strength of the PE material, while the surface resistance was higher than that of Example 1, and the antistatic and conductive properties were poor.
[0053] In Comparative Example 4, styrene is used to melt-graft polyethylene. Polystyrene molecular chains are introduced into the side chains of polyethylene, which can play the role of a compatibilizer, improve the compatibility between the SBS elastomer and the polyethylene resin, and help improve the mechanical properties of the PE material. However, the styrene-grafted polyethylene does not contain quaternary ammonium salt cations and cannot interact with the carboxylated carbon nanotubes. The compatibility between the carbon nanotubes and the SBS elastomer and the polyethylene resin is not improved, resulting in a lower reinforcement effect of the carbon nanotubes. The bending strength and impact strength of the PE material are lower than those in Example 1. In addition, the styrene-grafted polyethylene does not contain quaternary ammonium salts and polyhydroxy hydrophilic groups, and the surface resistance of the material is not well reduced. The surface resistance is greater than that in Example 1.
[0054] The surface of the carbon nanotubes added in Comparative Example 5 does not contain sodium carboxylate anions, and cannot interact with the quaternary ammonium salt cations of triethanolamine quaternary ammonium salt styrene grafted polyethylene, and does not improve the compatibility between the carbon nanotubes and the SBS elastomer and the polyethylene resin, resulting in a lower reinforcement effect of the carbon nanotubes, and lower bending strength and impact strength than Example 1. In addition, the carbon nanotubes have poor dispersion in the PE material matrix, and a continuous conductive path is not well formed, resulting in a surface resistance higher than Example 1.
[0055] Comparative Example 6 uses N-triethyl-(4-vinylbenzyl)ammonium chloride to graft-modify the polyethylene resin, which does not contain polyhydroxy hydrophilic groups, resulting in the surface resistance of the PE material being slightly higher than that of Example 1.
Claims
1. A conductive PE material with good shock resistance and low resistance, characterized in that: The conductive PE material comprises 100 parts by weight of polyethylene resin, 10-35 parts by weight of SBS elastomer, 1.2-5 parts by weight of triethanolamine quaternary ammonium salt styrene grafted polyethylene, 1-6 parts by weight of carboxylated carbon nanotubes, and 0.3-0.5 parts by weight of antioxidant; The preparation method of triethanolamine quaternary ammonium salt styrene grafted polyethylene comprises the following steps: adding polyethylene resin, 4-vinylbenzyl triethanolamine quaternary ammonium salt and dicumyl peroxide into a twin-screw extruder for melt grafting, discharging the material, adding the product into xylene, heating to reflux, stirring and dissolving, then adding acetone for precipitation, extracting the precipitate with acetone in a Soxhlet extractor, and drying to obtain triethanolamine quaternary ammonium salt styrene grafted polyethylene.
2. The conductive PE material with good shock resistance and low resistance according to claim 1, characterized in that: The mass ratio of the polyethylene resin, styryl triethanolamine quaternary ammonium salt and dicumyl peroxide is 100:(4-15):(0.2-0.8).
3. The conductive PE material with good shock resistance and low resistance according to claim 1, characterized in that: The temperature during the melt grafting is 175-185° C. and the time is 4-8 minutes.
4. The conductive PE material with good shock resistance and low resistance according to claim 1, characterized in that: The preparation method of the 4-vinylbenzyltriethanolamine quaternary ammonium salt is as follows: 4-chloromethylstyrene and triethanolamine are added to acetonitrile, heated to 40-55° C. in a nitrogen atmosphere, reacted for 18-30 hours, concentrated under reduced pressure, and the product was recrystallized from a mixed solution of ethanol and ethyl acetate to obtain the 4-vinylbenzyltriethanolamine quaternary ammonium salt.
5. The conductive PE material with good shock resistance and low resistance according to claim 4, characterized in that: The molar ratio of the 4-chloromethylstyrene to triethanolamine is 1:(1-1.05).
6. The conductive PE material with good shock resistance and low resistance according to claim 1, characterized in that: The preparation method of the carboxylated carbon nanotubes comprises: adding carbon nanotubes to a nitric acid solution, heating to 50-60° C. after ultrasonic dispersion, reacting for 1-2 hours, filtering after cooling, adding the product to a sodium hydroxide solution, filtering after stirring, washing with water, and drying to obtain the carboxylated carbon nanotubes.
7. The conductive PE material with good shock resistance and low resistance according to claim 6, characterized in that: The mass fraction of the nitric acid solution is 60-68%.
8. A method for preparing a conductive PE material with good shock resistance and low resistance as claimed in any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: mixing polyethylene resin, SBS elastomer, triethanolamine quaternary ammonium salt styrene grafted polyethylene, carboxylated carbon nanotubes and antioxidant in a mixer, and then melting, mixing, extruding and pelletizing in a twin-screw extruder to obtain a conductive PE material with good shock resistance and low resistance.
9. The method for preparing a conductive PE material with good shock resistance and low resistance according to claim 8, characterized in that: The temperature of the mixer is 60-70°C, and the mixing time is 20-40 minutes; the melt blending temperature of the twin-screw extruder is 180-190°C, and the screw speed is 60-100r / min.
Citation Information
Patent Citations
Antistatic packaging material
CN114213744B
PE alloy material for heat and cold-resistant non-cracking traffic cone
CN109467785A
Cationic block polymer intercalation modifier, preparation method thereof and application of cationic block polymer intercalation modifier in building functional materials
CN112979894A
Polymer coatings that resist adsorption of proteins
US20100096327A1